THE EFFECT OF TRAINING AND MENTORING ON PERFORMANCE TEACHER WITH COMPENSATION AS A VARIABLE MODERATION IN PINTAR PROGRAM PARTNER SCHOOLS TANOTO FOUNDATION BATU BARA DISTRICT - Felly Ardan; Ritha F Dalimunthe; Parapat Gultom (CV. Radja Publika, 2024)
This research aims to analyze the effect of training and mentoring on teacher performance through providing compensation at Tanoto Foundation PINTAR Program partner schools in Batu Bara Regency. Data was collected through a survey using a questionnaire distributed to respondents as many as 72 Tanoto Foundation PINTAR Program partner school teachers in Batu Bara Regency. Data were analyzed using descriptive analysis and SEM (Structural Equation Model) analysis. The research results show that training has a positive and significant influence on teacher performance. Mentoring has a positive and significant effect on teacher performance. Compensation does not moderate the effect of training on teacher performance. The practical implication of this research is the importance of developing appropriate training and ongoing mentoring in improving individual performance. Apart from that, organizations also need to pay attention to compensation as a factor that can moderate the relationship between training and performance.